Editorial - From the campus to the classroom: University philosophy outreach programs - Michael Hand; Jane Gatley (Journal of Philosophy in Schools, 2023)
University philosophy outreach programs are proliferating. On campuses across the world, students and staff are taking philosophy out to the wider community, and especially to children and young people in schools. Their mission is to engage the public in philosophical discussion and to make a notoriously abstract and arcane subject accessible, meaningful and useful. As yet, there is little published research on these programs. They give rise to two clusters of questions deserving of scholarly attention. First, there are questions about the rationale for philosophy outreach. What is the purpose of taking philosophy into the community? What are the intended benefits of these programs, to the children and young people who participate in them, to the students and staff who lead them, to society at large, or to the discipline of philosophy itself? How do these aims inform the selection of philosophical topics, texts, tools and techniques? The second group of questions have to do with the success of philosophy outreach. What attempts have been made to evaluate these programs and their outcomes? Do they, in fact, yield the benefits intended by those who design and deliver them? Are there any drawbacks to participation, or benefits other than the intended ones? What challenges (financial, institutional, pedagogical, psychological) have been encountered by those engaged in philosophy outreach and how have they been overcome? These are the questions that animate this double special issue on university philosophy outreach programs. The tremendously positive response we received to our call for papers, from contributors in Europe, North America and Australasia, confirms our impression that these questions are ripe for scholarly attention. Here, in Issue 10(1) we present the first tranche of papers; the next tranche will follow later this year, in Issue 10(2).